Model-Driven Design Using IEC 61499: A Synchronous Approach for Embedded and Automation Systems - Yoong, L.H (Springer, 2015)
This book describes a novel approach for the design of embedded systems and industrial automation systems, using a unified model-driven approach that is applicable in both domains. The authors illustrate their methodology, using the IEC 61499 standard as the main vehicle for specification, verification, static timing analysis and automated code synthesis. The well-known synchronous approach is used as the main vehicle for defining an unambiguous semantics that ensures determinism and deadlock freedom. The proposed approach also ensures very efficient implementations either on small-scale embedded devices or on industry-scale programmable automation controllers (PACs). It can be used for both centralized and distributed implementations. Significantly, the proposed approach can be used without the need for any run-time support. This approach, for the first time, blurs the gap between embedded systems and automation systems and can be applied in wide-ranging applications in automotive, robotics, and industrial control systems. Several realistic examples are used to demonstrate for readers how the methodology can enable them to reduce the time-to-market, while improving the design quality and productivity.